PENGARUH PENGGUNAAN MODEL PEMBELAJARAN SNOWBALL THROWING TERHADAP KETERAMPILAN MENULIS RESENSI CERPEN SISWA KELAS XI IPA SMA NEGERI 9 KOTA JAMBI - Novi Yolanda Dwi Sapitri (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2020)
The purpose of this research is to find out the effect of using snowball throwing learning model towards students’ short story writing ability at class XI IPA SMA Negeri 9 Kota Jambi Academic year 2018/2019. The method of this research is quasi-experiment with quantitative approach which is used to measure the short story writing ability objectively. From the result of the research, it can be presented that the mean score of students’ post-test of experiment class is 83 and control class is 75.8. The normality test which is taken from expermient class score is 0,095 > 0,05 and control class score is 0,057 > 0,05. Meanwhile the homogeneity test is significant in which F 0,439 > from significance level (α = 0,05). The result of hypothesis testing is the value of tcount 4,045> ttable 2,000 so Ho is rejected and Ha is accepted. Thus, it can be concluded that there is a difference of students’ learning by using snowball throwing and conventional media. The students who used snowball got higher score compared with the students who used conventional media.